THE EFFECT OF ASYNCHRONOUS BLENDED PROBLEM-BASED LEARNING ON THE CRITICAL THINKING ABILITIES OF UNDERGRADUATE MIDWIFERY STUDY PROGRAM STUDENTS - Kusumawardani , Paramitha Amelia (International Journal Multidisciplinary (IJMI), 2024)
Asynchronous blended problem-based learning (ABLE-PBL) is a problem-based learning (PBL) learning innovation that can be used in midwifery educational institutions that have a limited number of teaching staff but still want to optimize the learning process and produce competent quality graduates by community needs. The research aims to determine the relationship between asynchronous blended problem-based learning and the critical thinking abilities of undergraduate Midwifery students at Muhammadiyah University of Sidoarjo. Quantitative research method using a cross-sectional approach. The research population was undergraduate midwifery students at Muhammadiyah University of Sidoarjo with a sample size of 37 students. The sampling technique used total sampling and data was analyzed using the Person Chi Square technique. The results of the research show that the implementation of asynchronous blended problem-based learning is categorized as good at 70.3%. Students' critical thinking abilities are in the high category, namely 67.7% and based on the Person Chi-Square test p-value <0.05. The research concludes that there is a relationship between asynchronous blended problem-based learning and the critical thinking abilities of undergraduate Midwifery study program students.